Behavioral Visibility: A new paradigm for organization studies in the age of digitization, digitalization, and datafication. Issue 12 (December 2020) - Leonardi, Paul M.; Treem, Jeffrey W.
The digitization, digitalization, and datafication of work and communication, coupled with social and technical infrastructures that enable connectivity, are making it increasingly easy for the behaviors of people, collectives, and technological devices to see and be seen. Such digital connectivity gives rise to the important phenomenon of behavioral visibility . We argue that studying the antecedents, processes, and consequences of behavioral visibility should be a central concern for scholars of organizing. We attempt to set the cornerstones for the study of behavioral visibility by considering the social and technological contexts that are enabling behavioral visibility, developing the concept of behavioral visibility by defining its various components, considering the conditions through which it is commonly produced, and outlining potential consequences of behavioral visibility in the form of three paradoxes. We conclude with some conjectures about the kinds of research questions, empirical foci, and methodological strategies that scholars will need to embrace in order to understand how behavioral visibility shapes and is shaped by the process of organizing as we catapult, swiftly, into an era where artificial intelligence, learning algorithms, and social tools are changing the way people work.